Link Path Analysis Komunikasi Gelombang Mikro Topologi Ring Area Kota Padang - Nasrul - - (Jurnal Ilmiah Poli Rekayasa, 2017)
The development of the telecommunication the rapidly and the increased the need for information , trigger the increasing number of system project communication and discharging radio frequency .This needs to a design and planning ripe to make the existing system can work optimal without any disturbance of discharging frequency two closely ( interference ) .At the end of this task using software aplication pathloss 5.0 to do design as well as performing calculations link budged in observance of some other factors such as the position of site, the height of the contours of, the condition of propagation , and device used .The end of this duty also using visual basic 2010 to assist in performing calculations link budged.In the design uses the topology of ring from the area of the Padang city was used in 6 ( six ) link , first bypass to tabing at a distance of link 3,59 km , tabing to minang plaza at a distance of link 1,87 km , minang plaza to hotel pangeran at a distance of link 2,48 km , hotel pangeran to simpang anduriang at a distance link 4,05 km , simpang anduriang tobalai baru at a distance of link 2,31 km and balai baru to bypass at a distance 3,75 km.